Philosophical bases of teaching about the nature of punishment - Shidlovsky, Andrei V. (Journal of the Belarusian State University. Law, 2020)
The author investigates the philosophical foundations of the doctrine of the essence of punishment as a social and legal phenomenon, and considers approaches to the nature of punishment in various worldview paradigms that determine the need for this phenomenon to exist in society. The author reveals the main philosophical concepts of punishment in the classical, sociological and educational-humanistic criminal-legal directions. The author justifies the right of punishment from the positions of indeterminism, mechanistic determinism and determinism. The author notes the influence of new methodologies and worldview approaches on the development of the modern doctrine of punishment and penitentiary law. It is concluded that the essence of social justice is determined by the system of values accepted by a particular society, which forms the central core in the understanding of any philosophical perspective.
Keywords: punishment; the social and legal nature of punishment; the philosophy of idealism and materialism; criminal law; indeterminism; mechanistic determinism; determinism; the law of punishment